Evaluasi Pembelajaran Informatika Di Era Digital: Analisis Efektivitas Asesmen Berbasis Teknologi - Najla Sabillillah; Selma Junita; Trissa Desilla; Zulfani Sesmiarni (Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid advancement of digital technology has brought significant changes to learning processes, including Informatics education, which requires more authentic, adaptive, and competency-based assessment aligned with 21st-century skills. In the digital era, technology-based assessment has become increasingly essential for measuring students’ computational thinking, digital literacy, and problem-solving abilities more comprehensively. However, its effectiveness in Informatics learning has not yet been fully optimized due to limitations in teachers’ digital competence, infrastructure readiness, and unequal utilization of digital platforms across educational institutions. This study employs a library research method by reviewing recent journal articles, conference proceedings, scholarly books, and educational regulations published within the last five years that are relevant to Informatics learning evaluation and digital assessment implementation. The purpose of this study is to analyze the effectiveness of technology-based assessment in improving the quality of Informatics learning evaluation and to identify the supporting and inhibiting factors in its implementation in the digital era. The findings indicate that technology-based assessment improves the accuracy of evaluation, provides immediate feedback, supports differentiated learning, and facilitates the assessment of both process and products simultaneously. Additionally, digital platforms enable teachers to monitor students’ learning progress in real time. However, its effectiveness is still influenced by teachers’ technological literacy, network stability, and the availability of devices in schools. In conclusion, technology-based assessment has strong potential to enhance the quality of Informatics learning evaluation, yet it must be supported by improved teacher competencies, strengthened digital infrastructure, and policies that encourage continuous assessment innovation.